Proceso de duelo y su influencia en el estado emocional de un adolescente de 14 años de la Parroquia Ricaurte - Barragán Ureña, Kennya Dayana (2023)
The present case study was carried out with the objective of determining if the grieving process influences the emotional state of a 14-year-old adolescent from the Ricaurte Parish. All this was carried out through the use of the clinical history, semi-structured interview, direct observation, and the application of psychological tests "Beck Depression Inventory", "Hamilton Anxiety Scale" and "Mini mental", together with the “CBT register of thoughts and emotions”. In addition, the qualitative methodology that was used in this work was aimed at studying the dependent and independent variables, also thanks to the implementation of CBT techniques, it was possible to meet the stated objective, on the other hand, through a therapeutic plan it was achieved modify those thoughts that the adolescent manifested during the psychological intervention, in this way it was possible to mitigate the emotional and behavioral problems of the patient due to the grieving process through which she is going through, finally the results obtained were the desired ones which were directed in the improvement of their quality of life, both personal and social, family and school.